2016
DOI: 10.1111/ruso.12090
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality, Processes of Adaptation, and Female Local Initiatives in Cash Crop Production in Northern Tanzania

Abstract: This article contributes to development research, as well as research studying inequality in agricultural systems. We use empirical data from an ethnographic study in the village of Mamba, in northern Tanzania (2006)(2007)(2008)(2009). This study analyzes the question of changing gender relations and the patriarchal constraints to collective action under market liberalization of cash crops. Our findings demonstrate that the shift to a market economy has influenced the nature of production relations, deepening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The vulnerability of women’s agricultural income, compared to men’s, is stressed by Mukhopadhyay (2018) attributing this phenomenon to the influence of social norms and amplified by agricultural trade liberalization. The division of labor attributing low value added agricultural jobs to women and high value added to men is seen as a main factor in a wage gap, though unlikely be challenged due to prevailing patriarchy thinking in rural regions ( Manzanera‐Ruiz et al, 2016 ). Gupta et al (2017) documented that women tend to increase market orientation of farms, thus allowing receiving fairer price for their production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The vulnerability of women’s agricultural income, compared to men’s, is stressed by Mukhopadhyay (2018) attributing this phenomenon to the influence of social norms and amplified by agricultural trade liberalization. The division of labor attributing low value added agricultural jobs to women and high value added to men is seen as a main factor in a wage gap, though unlikely be challenged due to prevailing patriarchy thinking in rural regions ( Manzanera‐Ruiz et al, 2016 ). Gupta et al (2017) documented that women tend to increase market orientation of farms, thus allowing receiving fairer price for their production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also in terms of farm work, the responsibilities of men and women differ. Men have a larger responsibility of cash crops, large livestock, long-term trees and land, while women are left to ensure food on the table from food crops and small livestock such as poultry (Manzanera-Ruiz et al, 2016). However, there is a close link between social and human capitals in terms of knowledge and information since women in sub-Saharan Africa in most cases have lower education, less access to extension and advisory services, networks and decision making bodies within the community (Farnworth & Colverson, 2015).…”
Section: Gender Aspectsmentioning
confidence: 99%
“…Although men's dominance in commercial crop cultivation is documented for some locations, women may have opportunities to individually or collectively produce for cash. This is frequently framed by gender struggles concerning income control (Mnimbo et al 2017;Manzanera-Ruiz et al 2016). With regard to the value chains investigated in this work, Fischer et al (2017) described women farmers as proponents of market-oriented leafy vegetable production.…”
Section: Participation and Gainsmentioning
confidence: 99%
“…Palacios-Lopez et al (2017, p. 57) found that the share of women's labour in agriculture is above 50% for all crops except fruits and vegetables, where the share is 45%. Others argue that women spend more time on childcare and domestic chores as compared with men, and therefore have fewer opportunities to allocate time to productive and income-generating activities (Manzanera-Ruiz et al 2016;Fox 2016). Apart from time, access to land, credit and extension are important prerequisites for value chain participation.…”
Section: Participation and Gainsmentioning
confidence: 99%